A new mandibulate termite Amitermes kavarattiensis sp. nov. (Blattodea: Isoptera: Termitidae) from Lakshadweep Island, India. (2nd January 2023) - Sengupta, Rituparna; Keloth, Rajmohana; Poovoli, Amina; Basak, Jayati; Tyagi, Kaomud; Prasad, Priya
ABSTRACT: The subterranean, mandibulate termite genus Amitermes Silvestri (Blattodea: Isoptera: Termitidae) is hitherto known from India by only two species, Amitermes belli Desneux and Amitermes baluchistanicus Akhtar. This paper describes a new species Amitermes kavarattiensis Rituparna, Rajmohana & Amina sp. nov. collected from the Lakshadweep Islands, India. Morphological comparisons with both the known species are provided. A dichotomous key to identify all the five Amitermes species of Oriental region is also appended herewith. Additionally, three sequences of the partial fragment of mitochondrial 16S rRNA gene of the new species and five sequences of Amitermes belli have been generated for the first time. A phylogenetic tree with available sequences of Amitermes species is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:E9743114-7B9E-4AE4-8750-90F86FC49EEE